A study on parking space utilization at the International Islamic University Malaysia - Kadar Hamsa, Abdul Azeez (IIUM Press, 2005)
Parking is undeniably one of the integral elements in the transportation system. It plays an essential part in determining the success of land use for transportation. Increase in vehicle ownership and mobility results in increased demand for parking facilities. It becomes a major urban land use problem when the demand exceeds supply. Failure to meet the supply will result in congestion and a serious setback in providing an efficient transportation system. This study provides an outline on parking characteristics, such as parking accumulation, parking occupancy, parking duration, parking turnover, and parking volume. However, emphasis will be given to the central complex since it is the most dominant and active area in the campus. This paper lays the foundation in studying parking facilities and its utilization in the campus.